Postnatal cytomegalovirus infection and bronchopulmonary dysplasia in very low birth weight infants: Influence of diagnostic criteria and viral load in a propensity score–matched cohort study - Zhihui Qiao; Yingying Bao; Jiajun Zhu (PLoS ONE, 2026)
Objective To determine the association between postnatal cytomegalovirus (pCMV) infection and bronchopulmonary dysplasia (BPD) under three different criteria as well as the impact of viral load on clinical outcomes in very low birth weight (VLBW) infants. Methods In this retrospective cohort study, the data for VLBW infants with pCMV infection were collected from de-identified medical records and matched 1:1 with non-infected controls using propensity score matching between January 1, 2014, and December 31, 2024, in a tertiary neonatal intensive care unit in China. The primary outcome was the association between pCMV and BPD according to the 2001 National Institute of Child Health and Human Development (NICHD), 2018 NICHD, and 2019 Neonatal Research Network (NRN) criteria. The secondary outcome was healthcare resource utilization stratified by viral load. Results Seventy-four infants with pCMV infection were matched to 74 infants without pCMV infection. After the adjustment for confounders, pCMV infection was not significantly associated with BPD defined by the 2001 NICHD criteria (adjusted odds ratio [aOR], 8.26; 95% confidence interval [CI], 2.14–31.85; p < 0.01). However, it was associated with BPD under both the 2018 NICHD and 2019 NRN criteria (aOR 11.05, 95% CI, 4.00–30.52; p < 0.001 for both). Moreover, pCMV was significantly associated with higher severity grades (moderate to severe 2001 NICHD: aOR, 10.32; Grade II–III per the 2018 NICHD: aOR, 11.47; Grades 2–3 per the 2019 NRN: aOR, 12.81; all p < 0.001). Infants with high viral loads (≥1.34 × 10 5 copies/mL) require significantly more healthcare resources than infants with low viral loads (all p = 0.001). Conclusions The association between pCMV infection and BPD was influenced by the diagnostic criteria. A higher cytomegalovirus load in VLBW infants was associated with more severe respiratory morbidity and greater healthcare utilization.